Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - Rodrigues, L. A.; Almeida, A. A.; Agrizii, A. P.; Pacheco, N.; Carvalho, B. C.R.; Zanatta, A. C. [UNESP]; Kohlhoff, M.; Torres, C. M.M.E.; Bressan, G. C.; Leite, J. P.V. (Taylor & Francis, 2024)
In the present study, we have evaluated the cytotoxic activity of 282 extracts from 72 native plant species of the Brazilian Atlantic Forest biome. As a result, Casearia arborea and Sorocea hilarii leaves extracts showed cytotoxic activity against three tumour cell lines tested (B16F10, SW480 and Jurkat). After bioassay-guided fractionation, the bioactive fractions were submitted to the dereplication study via High-performance Liquid Chromatography, connected to High-resolution Mass Spectrometry (HPLC-ESI-QTOF/MS) analysis, combined with a Global Natural Products Social Molecular Networking (GNPS) tool. A combination of bioactivity-guided and dereplication approaches resulted in the putative annotation of 27 clerodane diterpenes and 9 flavonoids as main compounds present in the cytotoxic fractions of C. arborea. Regarding the active fraction of S. hilarii, 10 megastigmans, 17 spirostane steroids derivatives and 2 lignans were putatively identified. In conclusion, Casearia arborea and Sorocea hilarii are potential sources of antitumor compounds.
Keywords: Casearia arborea; Cytotoxic; dereplication; GNPS; Sorocea hilarii